The Influence of Tiktok Live Streaming, Customer Trust, and Customer Engagement on Electronic Product Purchase Decisions: The Mediating Role of Flow Experience among Followers of Tiktok @Kohcun - Amira, Nabila; Hafasnuddin; Nizam, Ahmad (International Journal of Scientific Research and Management (IJSRM), 2025)
This study investigates the influence of TikTok live streaming, customer trust, and customer engagement on electronic product purchase decisions, with flow experience serving as a mediating variable. A quantitative, causal research design was employed, using data collected from an online questionnaire administered to 264 followers of the TikTok account @Kohcun who had purchased electronic products through live streaming. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results reveal that TikTok live streaming, customer trust, and customer engagement each have a positive and significant effect on purchase decisions. Moreover, these three variables also exert a positive influence on flow experience. Flow experience itself was found to have a direct and significant impact on purchase decisions. Ultimately, flow experience was identified as a partial mediator in the relationships between TikTok live streaming, customer trust, customer engagement, and purchase decisions.